Surface Co‐Modification of Halide Anions and Potassium Cations Promotes High‐Rate CO2‐to‐Ethanol Electrosynthesis. Issue 39 (25th August 2022) - Peng, Chen; Yang, Songtao; Luo, Gan; Yan, Shuai; Shakouri, Mohsen; Zhang, Junbo; Chen, Yangshen; Li, Weihan; Wang, Zhiqiang; Sham, Tsun‐Kong; Zheng, Gengfeng
Abstract: The high‐rate electrochemical CO2 conversion to ethanol with high partial current density is attractive but challenging, which requires competing with other reduction products as well as hydrogen evolution. This work demonstrates the in situ reconstruction of KCuF3 perovskite under CO2 electroreduction conditions to fabricate a surface fluorine‐bonded, single‐potassium‐atom‐modified Cu(111) nanocrystal (K–F–Cu–CO2 ). Density functional theory calculations reveal that the co‐modification of both F and K atoms on the Cu(111) surface can promote the ethanol pathway via stabilization of the CO bond and selective hydrogenation of the CC bond in the CH2 CHO* intermediate, while the single modification of either F or K is less effective. The K–F–Cu–CO2 electrocatalyst exhibits an outstanding CO2 ‐to‐ethanol partial current density of 423 ± 30 mA cm −2 with the corresponding Faradaic efficiency of 52.9 ± 3.7%, and a high electrochemical stability at large current densities, thus suggesting an attractive means of surface co‐modification of halide anions and alkali‐metal cations on Cu catalysts for high‐rate CO2 ‐to‐ethanol electrosynthesis. Abstract : A surface fluorine‐bonded, single potassium‐atom‐modified Cu(111) nanocrystal (K–F–Cu–CO2 ) is prepared by in situ electrochemical reconstruction of KCuF3 perovskite. The K–F–Cu–CO2 electrocatalyst exhibits a CO2 ‐to‐ethanol partial current density of 423 ± 30 mA cm −2 with corresponding Faradaic efficiency of 52.9 ± 3.7%, and a high electrochemical stability at large current densities.